Estudo de associação genética em larga escala identifica potenciais regiões candidatas para o bruxismo do sono - Amaral Junior, Rosalvo [UNIFESP] (2017)
Introduction: Sleep bruxism is usually associated with excessive dental attrition and fractures or other health problems, such as morning headaches, muscle pain and increased risk of some temporomandibular disorders. Some evidence suggests that its pathophysiology may be influenced by genetic factors. Objectives: The present study aimed to evaluate potential polymorphisms, genes and biological pathways associated with sleep bruxism. Methods: It was performed a cross-sectional genome-wide association study with 75 sleep bruxism cases and 568 controls, all of them extracted from EPISONO cohort. Sleep bruxism was diagnosed by polysomnography and questionnaires. The DNA of all individuals was extracted from peripheral blood and 730,025 single nucleotide polymorphisms (SNPs) were genotyped through microarrays. Results: The results showed 2 SNPs associated with sleep bruxism with significance level <10-5: rs741448 located in 19q12 (p=5.12 x10-6); rs1721781 located in 2p22.3 (p=7.18 x10-6) and 38 SNPs with significance <10-4. In addition, through gene pathway and biological pathway analysis, associations with genes such as EPN3 (Epsin 3) with significance level <10-4 and biological pathways such as Melanin biosynthesis with significance level 10-3 were found between others not yet explored by pathophysiological hypothesis of sleep bruxism. Conclusions: This is the first study that identified genetic association with sleep bruxism. When replicated, it may point to new hypotheses in the pathophysiology of sleep bruxism.